6:
a: =>x-3/4=18/8=9/4
=>x=9/4+3/4=3
b: =>7/8:x=5/2
=>x=7/8:5/2=7/8*2/5=14/40=7/40
c: =>x+1/6=3/4
=>x=3/4-1/6=9/12-2/12=7/12
`@` `\text {Ans}`
`\downarrow`
`5,`
`a)`
\(x+2\dfrac{3}{4}=5\dfrac{2}{3}\)
`=> x = 5 2/3 - 2 3/4`
`=> x = 17/3 - 11/4`
`=> x = 35/12`
Vậy, `x = 35/12`
`b)`
\(x-1\dfrac{4}{5}=3\dfrac{2}{7}\)
`=> x = 3 2/7 + 1 4/5`
`=> x = 23/7 + 9/5`
`=> x = 178/35`
`c)`
\(x\times3\dfrac{1}{2}=4\dfrac{3}{4}\)
`=> x = 4 3/4 \div 3 1/2`
`=> x = 19/4 \div 7/2`
`=> x = 19/14`
Vậy, `x = 19/14`
`d)`
\(x\div2\dfrac{2}{3}=4\dfrac{1}{3}\)
`=> x = 4 1/3 \times 2 2/3`
`=> x = 13/3 \times 8/3`
`=> x = 104/9`
Vậy, `x = 104/9`
`6,`
`a)`
`x - 3/4 = 6 \times 3/8`
`=> x - 3/4 = 9/4`
`=> x = 9/4 + 3/4`
`=> x = 11/4`
Vậy,` x = 11/4`
`b)`
`7/8 \div x = 3 - 1/2`
`=> 7/8 \div x = 5/2`
`=> x = 7/8 \div 5/2`
`=> x = 7/20`
Vậy, `x = 7/20`
`c)`
`x + 1/2 \times 1/3 = 3/4`
`=> x + 1/6 = 3/4`
`=> x = 3/4 - 1/6`
`=> x = 7/12`
Vậy, `x = 7/12.`